2019
DOI: 10.1016/j.neulet.2019.134385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flashing stimuli shape and colour heterogeneity using a P300 brain-computer interface speller

Abstract: Objective: Previous works using a visual P300-based speller have reported an improvement modifying the shape or colour of the presented stimulus. However, the effects of both blended factors have not been yet studied. Thus, the aim of the present work was to study both factors and assess the interaction between them.Method: Fifteen naïve participants tested four different spellers in a calibration and online task. All spellers were similar except the employed illumination of the target stimulus: white letters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Different variations on the highlighting type and nature of the characters have been studied, such as the shape, color and size of the characters (Salvaris and Sepulveda, 2009;Ryan et al, 2017;Fernández-Rodríguez et al, 2019b) in order to improve system performance (classification accuracy, information transfer rate or ERP amplitude). Regarding the nature of stimuli, it has been demonstrated that the presentation of famous faces (FF) instead of letters leads to an improvement in performance (Kaufmann et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Different variations on the highlighting type and nature of the characters have been studied, such as the shape, color and size of the characters (Salvaris and Sepulveda, 2009;Ryan et al, 2017;Fernández-Rodríguez et al, 2019b) in order to improve system performance (classification accuracy, information transfer rate or ERP amplitude). Regarding the nature of stimuli, it has been demonstrated that the presentation of famous faces (FF) instead of letters leads to an improvement in performance (Kaufmann et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One study reported better performance and larger ERPs in block-shaped stimuli than letter-shaped because the block stimuli were larger. 67 Another study reported larger P300 in face stimuli than size matched nonface stimuli and larger P300 in large nonface stimuli than small nonface stimuli although performance did not differ between the conditions. 68 Our study has extended these findings to ALS patients.…”
Section: Discussionmentioning
confidence: 93%
“…Count References BCI2000 41 [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41] G-tec 29 [2], [42], [43], [7], [9], [10], [44], [45], [46], [23], [47],…”
Section: Devicesmentioning
confidence: 99%
“…SWLDA 38 [1], [2], [7], [9], [10], [13], [14], [17], [18], [20], [22], [24], [26], [32], [42], [43], [46], [48], [57], [59], [64], [65], [66], [68], [69], [73], [75], [86], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99] SVM 27 [4], [6], [13], [15], [16], [25], [27], [30], [39], [41], [64], [76], ...…”
Section: Models Count Referencesunclassified